2019
DOI: 10.1002/app.48316
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of graphene oxide modified polycarboxylic by in situ polymerization

Abstract: Graphene oxide (GO) was modified by in situ esterification reaction with isopentenol polyoxyethylene ether (IPEG) to obtain GO precursor (GO‐IPEG) with some polymerization activity. GO‐modified polycarboxylic (GO‐PCE) was prepared by GO‐IPEG and acrylic acid (AA) using the method of in situ polymerization. The molecular structure of GO‐IPEG and GO‐PCE was characterized by Fourier transform infrared spectroscopy (FTIR), Raman spectra, and nuclear magnetic resonance (NMR). The dispersion properties and dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The polyether macromonomers used in the production of PCE mainly include methoxy‐PEG, allyl‐PEG, methallyl‐PEG (HPEG), and isoprenol‐PEG (IPEG) macromonomers. According to the usage statistics, HPEG and IPEG are still the most commonly used macromonomers, when such two macromonomers be used to synthesize PCE, a heating reaction process is usually employed (the reaction temperature is 30–60 °C, even 80 °C sometimes), and the production cycle is about 4–5 h . By analyzing the structure of these two commonly used macromonomers, it can be found that they are all the same type of vinyl alcohol‐based macromonomers because their starting agents are both vinyl alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…The polyether macromonomers used in the production of PCE mainly include methoxy‐PEG, allyl‐PEG, methallyl‐PEG (HPEG), and isoprenol‐PEG (IPEG) macromonomers. According to the usage statistics, HPEG and IPEG are still the most commonly used macromonomers, when such two macromonomers be used to synthesize PCE, a heating reaction process is usually employed (the reaction temperature is 30–60 °C, even 80 °C sometimes), and the production cycle is about 4–5 h . By analyzing the structure of these two commonly used macromonomers, it can be found that they are all the same type of vinyl alcohol‐based macromonomers because their starting agents are both vinyl alcohol.…”
Section: Introductionmentioning
confidence: 99%